Optimizing the Productive Utilization of Zakat in the Youth Ekselensia Scholarship Dompet Dhuafa: A Most Significant Change (MSC) Approach - Yulianti, Yulianti; Fitria, Lia; Haryadi, Pedri (International Journal of Zakat, 2025)
Educational scholarship support for the young generation in Indonesia is a much-needed support for now. Although the government has provided support through the 12-year free learning program, however, high school students still need educational assistance support in preparing for higher education. The Youth Ekselensia Scholarship program is present through the utilization of productive zakat to support high school students preparing to qualify for their dream state university. Productive zakat is the utilization of zakat through productive management and empowerment processes, which in practice is carried out by distributing capital to mustahik which is then managed to fulfill their welfare in the future. In this study, the researcher focuses on the utilization of productive zakat through educational empowerment. “This study aims to analyze how productive zakat can be optimized through educational empowerment within the Youth Ekselensia Scholarship (YES) program. In this research method, the researcher uses descriptive qualitative research and data analysis techniques using the Most Significant Change (MSC) approach. The results of this study show that the Youth Ekselensia Scholarship program shows a significant optimization through the utilization of productive zakat. This can be seen from the achievements of the beneficiaries of the Youth Ekslensa Scholarship program who have successfully qualified for well-known state universities in Indonesia. In addition, the optimization of the Youth Exlensia Scholarship program can be seen from the satisfaction of the beneficiaries of the YES Program from each activity. In batch 1, the average satisfaction level obtained by the beneficiaries of the YES program was 90.56%. Meanwhile, in batch 2, the average level of satisfaction obtained by the beneficiaries of the YES program was 73.27%.